ANALISIS VEGETASI PADA HABITAT RUSA BAWEAN (AXIS KUHLII MULL. ET. SCHLEG) DI PULAU BAWEAN - Mansur, Muhammad (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2004)
Bawean Island is a remote and tiny island, located approximately 150 km north of Surabaya. In this island it is known to habituate an endemic deer called Bawean deer (Axis kuhlii Mull. Et. Schleg). The animal is protected both nationally and internationally. Understanding the forest as the habitat for this deer is an important step toward the management and the development of the whole habitat. This study was conducted on September 2001 in three locations, known to be the habitat for Bawean deer, that was the Kumalasa, Patarselamat and Pudakit Barat villages. The forest type at study sites was lowland secondary forest. There were 114 species from 90 genus and 56 families. Number of species and trees density at Audacity Barat villages are bigger than Patarselamat or Kumalasa villages. In all study sites, Syzygium lepidocarpa, Irvingia malayana, Garcinia dioica, and Microcos tomentosa are common species.Trees height in three location were under 25 m tall, and stem diameter class were highest among 10-20 cm. Species richness (Ss) ranged from 22,7 to 55,7%. The plant communities in Patarselamat and Pudakit Barat were relatively same, but different with Kumalasa village.